Subtract:
$(i)$. $-5y^2$ from $y^2$
$(ii)$. $6xy$ from $-12xy$
$(iii)$. $(a-b)$ from $(a+b)$
$(iv)$. $a(b-5)$ from $b(5-a)$
$(v)$. $-m^2+5mn$ from $4m^2-3mn+8$
$(vi)$. $-x^2+10x-5$ from $5x-10$
$(vii)$. $5a^2-7ab+5b^{2}$ from $3ab-2a^2-2b^2$
$(viii)$. $4pq-5q^2-3p^2$ from $5p^2+3q^2-pq$

AcademicMathematicsNCERTClass 7

To do: To subtract: 
$(i)$. $-5y^2$ from $y^2$

$(ii)$. $6xy$ from $-12xy$

$(iii)$. $(a-b)$ from $(a+b)$

$(iv)$. $a(b-5)$ from $b(5-a)$

$(v)$. $-m^2+5mn$ from $4m^2-3mn+8$

$(vi)$. $-x^2+10x-5$ from $5x-10$

$(vii)$. $5a^2-7ab+5b^{2}$ from $3ab-2a^2-2b^2$

$(viii)$. $4pq-5q^2-3p^2$ from $5p^2+3q^2-pq$

Solution:

i) $-5y^2$ from $4y^2$

$=y^{2\ }-(-5y^2)$

$=y^2+5y^{2\ }=\ 6y^2$

ii) $6xy$ from $-12xy$

$=-12xy-(6xy)$

$=-18xy$

iii) $(a-b)$ from $(a+b)$

$=(a+b)-(a-b)$

$=2b$

iv) $a(b-5)$ from $b(5-a)$

$=b(5-a)-a(b-5)$

$=5b-ab-ab+5a$

$=5a+5b-2ab$

v) $-m^2+5mn$ from $4m^2-3mn+8$

$=(4m^2-3mn+8)-(-m^2+5mn)$

$=4m^2+m^2-3mn-5m+8$

$=5m^2-8mn+8$

vi) $-x^2+10x-5$ from $5x-10$

$=(5x-10)-(-x^2+10x-5)$

$=x^{2}+5x-10x-10+5$

$=x^{2}-5x-5$

vii) $5a^2-7ab+5b^{2}$ from $3ab-2a^2-2b^2$

$=(3ab-2a^2-2b^2)-(5a^2-7ab+5b^2)$

$=3ab+7ab-2a^2-5a^2-2b^2-5b^2$

$=10ab-7a^2-7b^2$

viii) $4pq-5q^2-3p^2$ from $5p^2+3q^2-pq$

$=(5p^{2}+3q^2-pq)-(4pq-5q^2-3p^2)$

$=5p^{2}+3p^2+3q^2+5q^2-pq-4pq$

$=8p^{2}+8q^2-5pq$
raja
Updated on 10-Oct-2022 13:38:20

Advertisements